Student perception towards in-class simulation games: A case of hospitality investment simulation / Mohd Hafiz Hanafiah and Mohd Raziff Jamaluddin - Hanafiah, Mohd Hafiz; Jamaluddin, Mohd Raziff (Universiti Teknologi MARA Selangor and UiTM Press, 2018)
This research note emphasis on the adoption of simulation games in financial classes. This research reports the perception of Faculty of Hotel and Tourism Management (FPHP) students attending the Hospitality Financial Management for Hospitality Management subjects. Previous studies claimed that classroom games and simulation increase students’ knowledge and interest level. However, only a few researchers focus on whether students’ performance was improved after attending such simulation games. A structured questionnaire was distributed to 191 final‐year FPHP undergraduates. The survey assessed students’ perceived ease of use, perceived usefulness, attitude and enjoyment with HIS and their examination result. This research found student performance correlate with their perception towards the investment simulation games.